Hyperarid soil microbial community response to simulated rainfall - Demergasso, Cecilia; Neilson, Julia W.; Tebes-Cayo, Cinthya; Véliz, Roberto; Ayma, Diego; Laubitz, Daniel; Barberán, Albert; Chong-Díaz, Guillermo; Maier, Raina M. (Frontiers in Microbiology, 2023)
The exceptionally long and protracted aridity in the Atacama Desert (AD), Chile, provides an extreme, terrestrial ecosystem that is ideal for studying microbial community dynamics under hyperarid conditions. Our aim was to characterize the temporal response of hyperarid soil AD microbial communities to ex situ simulated rainfall (5% g water/g dry soil for four weeks) without nutrient amendment. We conducted replicated microcosm experiments with surface soils from two previously well-characterized AD hyperarid locations near Yungay at 1242 and 1609 masl (YUN1242 and YUN1609) with distinct microbial community compositions and average soil relative humidity levels of 21% and 17%, respectively. The bacterial and archaeal response to soil wetting was evaluated by 16S rRNA gene qPCR, and amplicon sequencing. Initial YUN1242 bacterial and archaeal 16S rRNA gene copy numbers were significantly higher than for YUN1609. Over the next four weeks, qPCR results showed significant increases in viable bacterial abundance, whereas archaeal abundance decreased. Both communities were dominated by ten prokaryotic phyla (Actinobacteriota,